Development of software for analysis of indicators of spatial development of a complicated subject territory - Sizov, Alexander; Chernykh, Elena (E3S web of conferences, 2021)
The article is devoted to the description of the created software package that allows the user to solve a number of problems of systematization and primary processing of a large volume of spatial data on three subjects of the Tyumen region included in the statistical register of Rosstat for a given monitoring period in order to calculate and analyze indicators of the spatial development of the territory of the “Greater Tyumen region”